Study Protocol on Cognitive Performance in Bulgaria, Croatia, and the Netherlands: The Normacog Brief Battery - Jakob, Lea; Bojanić, Lana; Tsvetanova, Desislava D.; Buabang, Eike K.; de Bles, Nienke J.; Sarafoglou, Alexandra; Dijkzeul, Annet; Del Pino, Rocio (Frontiers in Psychology, 2016)
The Normacog Brief Battery (NBB) provides a comprehensive overview of an individual’s cognitive functioning within a short amount of time. It was originally developed for the Spanish population in Spain. However, there is a considerable need for brief batteries in clinical neuropsychological assessment, especially in eastern European countries. Cultural background and other individual characteristics—such as age, level of education, and sex—are shown to influence both cognition and patients’ performance on neuropsychological tests. Therefore, it is important to develop understanding of how and why culture impacts on cognitive testing and determine which sociodemographic variables affect cognitive performance. The current study aims to translate, adapt, and standardize the NBB in Bulgaria, Croatia, and the Netherlands, and to analyze the effect of sex, age, and education level on cognitive performance between these three countries. This brief battery assesses eleven cognitive domains, including those most currently relevant in cognition such as premorbid intelligence, attention, executive function, processing speed, and memory. The translation and adaptation of the battery for different cultures will be done using the back-translation process. After exclusion criteria, the current study will include a total sample of three hundred participants (≥18 years old). The samples of 100 participants per country will be balanced through the consideration of their age and level of education. Effects of the sociodemographic variables (age, level of education, and sex) on cognitive performance are expected. Furthermore, this relationship is expected to differ across countries. A multivariate hierarchical linear regression will be used and exploratory analysis will be carried out to investigate further effects. The results will be particularly valuable for future research and assessment in cognitive performance. The growing demand for accurate and fast neuropsychological assessment shows the importance of creating a universal brief assessment tool for wider cross-cultural application.